Estrategias financieras para mejorar los niveles de rentabilidad y liquidez en la empresa “Mega Compu” de la ciudad de Tulcán. - Ipial Cárdenas, Diana Milena (2014)
The inefficiency of financial management processes currently applied in the company of study, that monitor and control the financial and economic situation affect the profitability situation when compared with the costs of market opportunity, also affected the level liquidity in the company. causing problems in meeting short-term obligations. The above implies the need of solving the correspondence inadequate financial management to achieve the quality of their processes and excellence in the results, so it shows the picture that is a scientific problem that requires a deep investigation of theoretical - practical tools and specific conditions where they will be applied, By virtue of the problem, formulated the idea to defend in this paper, which shows that the design of financial strategies to enhance profitability and liquidity level in the company "Mega Compu” Tulcán cily, trying bo collect technical procedures that optimize the use of resources and help identify operational problems, financial or reflect trends that may affect the future. In keeping with the idea to defend raised, the overall objective of the research guides the activities to be performed; consisting of procedures and support tools, based on the basis of a conceptual model, a model of qualitative research - cuantitavo, based on a methodology systematic and holistic approach helps to formulate appropriate strategies, guiding the research line Financial Management and Social Responsibility.